Land Bank in Indonesia: Disoriented Authority, Overlapping Regulations and Injustice - Mahfud, Muh Afif; Djohan, Naufal Hasanuddin; Malik, Muhammad Fahad (Universitas Negeri Gorontalo, 2024)
The Indonesian Lank Bank Agency (â€œLand Bankâ€) is a sui generis institution that has broad authority including providing convenience for investors and implementing agrarian reform based on the value of justice and legal certainty. This paper aims to analyze the disorientation of authority and overlapping regulations of the Land Bank, examine the Land Bank's authority based on the cybernetic concept of Talcott Parsons and deconstruct the Land Bankâ€˜s authority in terms of the value of justice. This research is a normative study that uses secondary data collected through literature research and analyzed the data through content analysis. Based on the analysis, it is found that there is a disorientation of the Land Bankâ€˜s authority as its authority to implement the agrarian reform aimed at creating equitable land ownership is contradictory to its authority to facilitate investments that use large areas of land. The implementation of agrarian reform by the Land Bank also faces overlapping regulations and authority. Based on Talcott Parsons' cybernetic concept, the Indonesian government prioritizes investment facilitation authority (economic subsystem) which has the highest energy and therefore ignore agrarian reform (social subsystem) which has lower energy. This is not in line with the principle of justice, namely partiality to the disadvantaged party since it prioritizes the interests of business entities as the more economically advantaged party and overrides the interests of people who do not own land or control land less than the minimum limit.